THE EFFECT OF 20% DUCK EGG (Anas platyrhynchos domesticus) NANOHYDROXYAPATITE EXTRACT GEL ON MICROPOROSITY OF EROSIONED PERMANENT TEETH - Glenis Grytha Qothrunnada; Prima Agusmawanti; Rina Kartika Sari (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Dental erosion is a non-carious lesion that occurs due to demineralization caused by exposure to acidic materials. The tooth remineralization process can be restored by adding calcium-containing materials to the teeth. There are other sources of calcium that come from animals but are still not and are rarely explored, one of which is duck egg shells. Duck egg shells contain around 94 – 97% CaCO3 and the content of duck egg shells reaches 90% calcium levels. Method: The experimental research design was in the form of a post test only control group design with a total sample of 12 permanent premolars. Duck egg shell nanohydroxyapatite is given in a gel preparation. Tooth microporosity was measured using a Scanning Electron Microscopy with a micro magnification of 5000x Result: The hypothesis test was carried out by using the one way ANOVA test and significant results were obtained (P≤ 0.05) for all treatment groups. The LSD test was carried out to see the differences between groups and the results obtained between the group of 20% duck egg shell extract gel, 5% sodium fluoride and the untreated group obtained a p value = 0.000 (p